PEMANFAATAN LIMBAH GERGAJIAN INDUSTRI KAYU MERBAU (Intsia sp) MENJADI BRIKET ARANG - Elisabeth Payung Allo; Agustinus; Herlando Sinaga (Jurnal Biogenerasi, 2023)
Industrial merbau wood sawn waste has not been utilized as an alternative fuel. The increase in fuel prices is a policy dilemma for the government and currently subsidies have been abolished, because most of them only benefit the upper class and industry. The problems faced by both rural and urban communities are due to the expensive and unaffordable price of fuel, delays in supply which result in scarcity and long queues to get fuel. Sawn waste is a problem for the PT industry. Global Mandiri, which has not been used or managed, causing environmental pollution. With these conditions the author was moved to raise the problem through thought, by utilizing sawn timber industrial waste as an energy source around community settlements which is quite abundant as an alternative energy source. The purpose of this study was to obtain the quality of charcoal briquettes from sawdust of merbau wood as an alternative fuel. The research method used was an experimental method with 3 treatments, namely 5%, 4%, and 3% adhesives with a loading of 2000 lbm, 2500 lbm, 3000 lbm. The results of this study indicated that the density values ​​of charcoal briquettes were 0.714 and 0.789 gr/m3 at a concentration of 5% adhesive. At 4% adhesive concentration, the density values ​​were 0.771 gr/m3 and 1.054 gr/m3. For an adhesive concentration of 3%, the briquette density values ​​were obtained at 1.046 gr/m3 and 1.121 kg/m3. Of the three treatments, it is not close to the standard SN density value. Likewise, the water content obtained was 11.26%, which was not included in the SN. For the highest ash content, 8.3% is included in the SN standard. The results of the briquettes burning test showed that there was no smoke, no cracks, and did not quickly produce high ash and coal. The weight of the tested briquettes was 36.31 grams and it took 1.16'52 "hours to burn them to ashes. So that this research can be used as a suggestion in the manufacture of charcoal briquettes